A case report of empty Sella syndrome secondary to Hantaan virus infection and review of the literature. Issue 14 (April 2020) - Chen, Haiying; Li, Yuxiang; Zhang, Peng; Wang, Yang
Abstract: Rationale: Bleeding in the anterior pituitary lobe leading to tissue necrosis occurs in the acute stage of severe clinical forms of hemorrhagic fever with renal syndrome (HFRS), while atrophy of the anterior pituitary lobe with diminution of the gland function occurs after the recovery stage. The relationship between Hantaan virus infection and empty Sella syndrome (ESS) has rarely been reported. Patient concerns: This patient was a 54-year-old previously healthy Chinese male. He presented with fever, headache, and backache with dizziness and oliguria. Physical examination was notable for hypotension and the signs of conjunctival suffusion. His platelets decreased, and his urine protein was positive. Hantaan virus IgM and virus RNA were positive. Diagnosis: He was diagnosed as having HFRS. In his diuretic phase, his 24-hour urine volume was maintained at 10, 000 mL, and his blood pressure was higher for a week. Then, he was diagnosed as having ESS after a series of examinations. Interventions: Hormone replacement therapy was given to this patient after the diagnosis "ESS" was made. Outcomes: The patient's symptoms improved, and he was discharged from the hospital soon after hormone replacement therapy. Lessons: Pituitary function examination and brain magnetic resonance imaging (MRI) need to be considered to scan for ESS and panhypopituitarism in the patients with HFRS accompanied by diabetes insipidus.